Bacterial dynamics and the prevalence of foodborne pathogens associated with the avocado fruit, Persea Americana Mill. in a food processing facility - Korsten, Lise (University of Pretoria, 2021)
Dissertation (MSc (Plant Pathology))--University of Pretoria, 2020.